The Comprehensive Systematic Review of Association of Positive Surgical Margins to Biochemichal Recurrence in Prostate Cancer - Andi Dedi Pradana Putra; Khaeriah B (The International Journal of Medical Science and Health Research, 2026)
Introduction: Positive surgical margins (PSM) following radical prostatectomy (RP) represent a critical prognostic factor in prostate cancer management, yet their precise impact on biochemical recurrence (BCR) and long-term oncological outcomes remains heterogeneous across studies. A systematic synthesis of the evidence is required to clarify this association and guide clinical decision-making. Methods: This comprehensive systematic review adhered to PRISMA guidelines, screening studies from multiple databases. Inclusion criteria encompassed observational studies or systematic reviews/meta-analyses investigating the PSM-BCR association in men undergoing RP for non-metastatic prostate cancer, with a minimum 6-month follow-up. Data extraction was performed systematically, focusing on study design, PSM and BCR definitions, patient demographics, surgical details, association findings, and the impact of adjuvant therapies. Results: The review incorporated 80 studies. PSM was consistently associated with a significantly increased risk of BCR, with pooled hazard ratios (HR) ranging from 1.35 to 2.37 in multivariate analyses (Zhang et al., 2018; Kim et al., 2022). The risk was modulated by PSM characteristics: Gleason grade 4/5 at the margin (HR 1.87 vs. grade 3), margin length >3mm (HR 1.99), and multifocality (HR 1.38) conferred higher BCR risk (Lysenko et al., 2020; John et al., 2023; Guo et al., 2024). PSM rates varied by surgical approach and pathological stage, with nerve-sparing techniques and surgeon experience influencing outcomes (Moris et al., 2021; Bianco et al., 2006). While adjuvant radiotherapy (RT) improved BCR-free survival, early salvage RT demonstrated comparable long-term metastasis-free and overall survival (Hackman et al., 2019; Schneider, 2020). Discussion: The heterogeneity in effect estimates is attributable to differences in study populations, methodological rigor, and the granularity of PSM characterization. PSM should not be interpreted in isolation but as part of a multimodal risk profile including pathological stage and Gleason grade. The evolving paradigm favors risk-adapted strategies, potentially reserving immediate adjuvant RT for the highest-risk profiles while employing early salvage for others. Conclusion: PSM is a significant, independent predictor of BCR after RP, but its prognostic weight is contingent upon specific margin characteristics and coexisting pathological features. Clinical management should integrate detailed margin assessment with other risk factors to personalize postoperative strategies, emphasizing refined risk stratification and judicious use of adjuvant therapies.